Two cases of breast angiosarcoma after breast conserving surgery - Eriko Shiraki; Yookija Kang; Takahiro Shibayama; Shigeru Tsuyuki (Surgical Case Reports, 2020)
Abstract Background Breast angiosarcoma (AS) is a rare malignant breast tumor arising from endothelial cells lining the blood vessels. The prognosis of AS is reportedly poor. However, the effectiveness of chemotherapy and radiation is still controversial. Surgery is the only curable treatment, and removal of AS with adequate surgical margin is important. Case presentation We report two cases of primary and radiation-induced breast angiosarcoma (AS) after performing breast conserving surgery (BCS) for breast cancer. In case 1, a 72-year-old woman underwent right BCS with adjuvant radiation therapy (RT) for breast cancer 5 years prior. She was diagnosed with AS of the right breast and underwent mastectomy with a wide skin resection of the breast. As the tumor cells were positive for c-myc, this tumor was diagnosed as a radiation-induced AS. In case 2, an 80-year-old woman underwent BCS without adjuvant RT. She was diagnosed with AS 3 years after BCS and underwent mastectomy with a wide skin resection of the breast. The tumor was diagnosed to be a primary AS because there were no episodes of RT or lymphedema. Both cases developed local recurrence within 1 year of surgery. Conclusion Our cases suggest that surgical margin is associated with the risk of local recurrence, and the difficulty of deciding a safe surgical margin should be set during preoperative diagnosis.